2023
DOI: 10.1007/s40171-023-00342-3
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Strategic Risk in Financial Institutions

Abstract: Banks face many intangible hazards that are difficult to calculate. Strategic risk is one of the most critical factors affecting a bank’s profitability, financial strength, and commercial success. The impact of risk on profit may be insignificant in the short term. Still, it may become highly significant in the medium and long term, with the potential to cause substantial financial losses and impair bank stability. Hence, strategic risk management is an important endeavor that must be carried out according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…During the analysis and evaluation of strategic risks, it was identified that companies without risk management systems do not utilize techniques to analyze and assess risks, confirming what has been previously found in the literature and highlighting the importance of having comprehensive risk management systems [35]. However, the leaders, based on their knowledge, experience, or external support, determine the level of priority of the risks.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…During the analysis and evaluation of strategic risks, it was identified that companies without risk management systems do not utilize techniques to analyze and assess risks, confirming what has been previously found in the literature and highlighting the importance of having comprehensive risk management systems [35]. However, the leaders, based on their knowledge, experience, or external support, determine the level of priority of the risks.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, it should be integrated into the strategy [4]. The adoption of risk management with an integrated approach has become increasingly relevant [35], replacing siloed work [36]; this trend is called ERM (Enterprise Risk Management), which is a process led by senior management and boards of directors that is applied in the design and deployment of a strategy. An ERM system is a valuable tool that managers should implement to manage corporate reputation and maintain high performance in corporate social responsibility [37].…”
Section: Strategic Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been argued that if the banking sector is too competitive, management's expectations of future revenues decline and thus favor conservative credit and investment policies, thus reducing commercial bank risk-taking. At the same time, when market resources are relatively limited in a highly competitive banking industry, commercial banks will improve their operational efficiency and risk prevention and control capabilities (Kedarya et al, 2023).…”
Section: The Moderating Effect Of Competitiveness In the Banking Sectormentioning
confidence: 99%